ECG body surface mapping in patients with gestational diabetes mellitus and optimal metabolic compensation - Žákovičová, Eva; Kittnar, Otomar; Slavíček, Jaroslav; Medová, Eva; Šváb, Přemysl; Charvát, Jiří (Physiological research, 2014)
Women with gestational diabetes mellitus (GDM) are at increased risk for cardiovascular diseases (CVD) events compared with women without GDM. The aim of the present study was to evaluate 200 parameters of the heart electric field in 35 women with GDM under optimal glycemic compensation compared to 32 healthy pregnant women. All examinations were performed in the 36th week of gestation. The parameters in ECG body surface mapping (BSM) were registered by the diagnostic system Cardiag 112.2. The absolute values of maximum and minimum in depolarization and repolarization isopotential, isointegral and isoarea maps were not significantly different between the groups. These findings correspond to the result of heart rate variability examination. However BSM revealed the significant prolongation of QRS complex (p=0.05), shortening of ventricular myocardial activation time (ICHVAT) (p=0.01), prolongation of mean QT duration (p=0.01) and increase of QT interval dispersion (p=0.01) in women with GDM. Duration of QRS and ICHVAT significantly correlated with interventricular septum and posterior wall thickness in GDM group, QTd interval correlated significantly with HbA1C level. We conclude that despite of optimal metabolic control several significant abnormalities detected by ECG BSM are still present in patients with GDM.
Keywords: gestační diabetes; Echocardiography; krevní glukóza; Heart Rate; Pregnancy; lidé; ženské pohlaví; mapování potenciálů tělesného povrchu; srdeční frekvence; studie případů a kontrol; Case-Control Studies; Blood Glucose; Female; Adult; Body Surface Potential Mapping; Humans; Diabetes, Gestational; dospělí; těhotenství; echokardiografie